The Chronotope of Tourism: Spaces and Rhythms - Nogués-Pedregal, Antonio Miguel (Revista de Antropología Social, 2012)
According to the World Tourism Organisation, international tourism will reach one billion in 2012. This complex compound of practices and devices that we name ‘tourism’ is a distinctive way to use space (territory, landscape) and time (rhythm, occurrences). Tourism is an important globalising agent because it contributes to extend globalization to where new information and communication technologies have not reached yet. Bakhtin’s concept of ‘chronotope’ is valuable to characterize the way spatial and time elements are combined in tourism contexts. The data induce that Tourism is the most perfect and sophisticated elaboration of Capitalism for it consumes places and territories, shapes landscapes and perpetuates dependency relationships. Besides, it also produces sense and meanings, it mediates place through tourism space and update spaces and rhythms according to the guiding principles of Global Market. To conclude some notes on the distinctiveness of anthropological practices as carried out in tourism environments are made.
Keywords: tourism; chronotope; signification; anthropological practice; globalisation